2010
DOI: 10.1111/j.1540-8159.2010.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Shock as a Determinant of Poor Patient‐Centered Outcomes in Implantable Cardioverter Defibrillator Patients: Is There More to It Than Meets the Eye?

Abstract: The medical benefits of the implantable cardioverter defibrillator (ICD) are well established, but ICD shocks are known to influence patient-centered outcomes. In this viewpoint, we examine the strength of the evidence as found in primary and secondary prevention trials that used quality of life as an outcome, and compare the influence of ICD shock with other factors (e.g., heart failure and psychological factors) as determinants of outcomes, with a view to providing recommendations for clinical practice and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…The effect of cardiac condition and the experience of shock varies from patient to patient and may not be as straightfor- ward as previously presumed. 5 Although some have suggested that there is little decrement to QoL after a single shock, debate exists as to whether it is premature to make conclusions regarding the effects of ICD shock. Especially given that the existing data are drawn from large, randomized, controlled trials predominantly using generic QoL measures that might not be as sensitive to detect the specific effects of shock.…”
Section: Conceptualization and Illustrative Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of cardiac condition and the experience of shock varies from patient to patient and may not be as straightfor- ward as previously presumed. 5 Although some have suggested that there is little decrement to QoL after a single shock, debate exists as to whether it is premature to make conclusions regarding the effects of ICD shock. Especially given that the existing data are drawn from large, randomized, controlled trials predominantly using generic QoL measures that might not be as sensitive to detect the specific effects of shock.…”
Section: Conceptualization and Illustrative Case Presentationmentioning
confidence: 99%
“…Finally, personality characteristics associated with negative emotional processes and social inhibition (type D personality) have also been established as prevalent (24%) in ICD patients and linked to increased risk of ventricular arrhythmia (hazard ratio, 1.89) and mortality (hazard ratio, 2:79). 5 Taken together, sufficient evidence exists to warrant the inclusion of psychosocial factors in the routine treatment planning of ICD patients.…”
Section: Prevalence and Impact Of Psychosocial Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies that evaluated the effects of both shocks and psychosocial factors, some have found that psychosocial factors, such as underlying personality traits, play a larger role than shocks in determining QOL for ICD patients. 15 Thus, it is likely that shocks interact with psychosocial factors such as personality traits and social support in influencing QOL for patients with ICDs.…”
Section: Psychosocial Impact Of the Icdmentioning
confidence: 99%
“…As with QOL, it is likely that many factors, such as baseline psychological traits and social support, interact with shock to impact whether patients develop anxiety, depression, or posttraumatic stress disorder. 7,15 Interventions to Improve Psychosocial Outcomes…”
Section: Psychosocial Impact Of the Icdmentioning
confidence: 99%